Penerapan manajemen asuhan keperawatan model tim dan model primer terhadap mutu asuhan keperawatan - Endah Indrawati; Erlena Erlena (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Nursing is a profesional service as an integral part of health care. Profesional nursing services can be realized if it is implemented by professional nursing staff so that they can contribute on improving hospital services quality, especially nursing services. Thus the method of providing nursing care is part of the organizing function. The method of providing nursing care consists of five methode which include functional method, case method, team method, modular method, and primary method.Purpose: To find out the effectiveness of the implementation of the team model and primary model of nursing care management on the quality of nursing care in the inpatient room of Karawang District Hospital.Method: Quasi experiment with pre post test design with group design with a total sample of 104 respondents. Data were analyzed using the GLM-RM test.Results: There was a significant difference in the team method group and the primary method group with a p value <0.05.Conclusion: The application of the team method and the primary method has an effect on improving the quality of nursing services.Keywords: Nursing Care Management; Team Model; Primary Models; Quality of Nursing Care.Pendahuluan: Keperawatan merupakan pelayanan profesional sebagai bagian integral dari pelayanan kesehatan. Pelayanan keperawatan profesional dapat terwujud apabila dilaksanakan oleh tenaga keperawatan yang profesional sehingga dapat berkontribusi dalam peningkatan kualitas pelayanan rumah sakit khususnya pelayanan keperawatan. Dengan demikian metode pemberian asuhan keperawatan merupakan bagian dari fungsi pengorganisasian. Metode pemberian asuhan keperawatan terdiri dari lima metode yang meliputi metode fungsional, metode kasus, metode tim, metode modular dan metode primer.Tujuan: Untuk mengetahui efektifitas penerapan manajemen asuhan keperawatan model tim dan model primer terhadap mutu asuhan keperawatan di ruang rawat inap RSUD Kabupaten Karawang.Metode: Quasi eksperimen dengan rancangan pre post test with group design dengan jumlah sampel 104 responden. Data dianalisis menggunakan uji GLM-RM.Hasil: Terjadi perbedaan yang signifikan pada kelompok metode tim dan kelompok metode primer dengan nilai p < 0,05.Simpulan: Penerapan metode tim dan metode primer ada pengaruh pada peningkatan mutu pelayanan keperawatan.